PERCEPTUAL MAPPING OF MID END SMARTPHONE USING MULTIDIMENSIONAL SCALLING ANALYSIS (CASE : OPPO, SAMSUNG, XIAOMI, AND ASUS) - Malonda, Alvincent .; Pangemanan, Sifrid S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: But as time goes by, smartphone users become selective for selecting smartphone and some companies try to develop the smartphone with affordable price that can be reached by various circles of people. This increases competition among smartphone companies in creating affordable and high quality smartphone products. This research aims to find out the positioning on perceptual mapping of mid end smartphone products through quantitative approach from a potential customer in manado by using the multi dimensional scalling. The sample of this research using non probability sampling with 120 respondents of consumers that has knowledge and experience of using various kind of top smartphone products. This research has indentified the positioning of samsung, Oppo, Xiaomi, and Asus in customer mind using multi dimensional scale and considered by 6 smartphones attributes. These results show that Samsung became the most preferred brand of smartphone consumers compared to other smartphone brands. Samsung should maintain or improve the quality and give more innovative by provide new smartphone with affordable price so the consumers in all type will be more prefered with the Samsung than other brands.Keywords: perceptual mapping, positioning, multi dimensional scaling analysis